ความพึงพอใจของพนักงานสินเชื่อในธนาคารออมสินเขตสมุทรสาครที่มีต่อระบบพิจารณาอนุมัติสินเชื่อ - ธนัฐ โกมาก (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to investigate satisfaction of the Government Saving Bank employees in Samutsakorn region towards Loan Origination and Process System (LOPs). The methodology applied to this study was the 4 dimensions of Delone and McLean’s Information System Success Model (2003), including Information Quality, System Quality, Service Quality, and User Satisfaction. Data were acquired from 70 samples who had been the Load Origination and Process (LOPs) users within the period starting from October 2013 to September 2014. The studied summary was presented hereafter. The findings showed that most respondents were female in the age of 21-31 years old with Master’s degree and worked in the operational positions. They used computer at the minimum length of 5 – 7 hours a day and all of them used to work on the CBS system. The respondents paid high level of concern to Information Quality dimension. They also paid high level of concern on its elements mentioning that LOPs showed the most update outputs or information, provided the accurate outputs or information, offered the right outputs or information according to the need of users, had the complete and valid outputs or information, and presented outputs or information in the practical format which was proper to the use of users, in orderly. The respondents paid moderate level of concern to System Quality dimension. The element that they paid high level of concern on was the simple function of LOPs which was easy to learn; while the element that they paid moderate level of concern was the flexible function of LOPs which could be adjusted according to the need of users. The respondents paid high level of concern to Service Quality dimension. They also paid high level of concern on its elements mentioning that IT system administrator could solve problems as declared, concentrated and paid attention to providing assistance to LOPs users, had adequate knowledge and command on solving any problems occurred, and was ready to offer assistance as soon as being requested, in orderly. The respondents paid high level of concern to the satisfaction towards LOPs system. They also paid high level of satisfaction towards its IT system administrator, its outputs or information, and its working system, in orderly. Result of the correlation test between Information Quality, System Quality, and Service Quality and User Satisfaction towards Loan Origination and Process System (LOPs) showed that Information Quality, System Quality and Service Quality correlated with User Satisfaction towards the application of LOPs at high level and in the positive way. Dimensions being found at high level of correlation were Information Quality, Service Quality and System Quality, in orderly. Result of the correlation test between Information Quality and Satisfaction towards Information Quality presented that elements on system’s accuracy, completeness, demanding responsiveness, update information and appropriateness to users correlated with the Satisfaction towards Information Quality at high level and in positive way. Elements found in high level of correlation were respectively ranked as follows: the system’s completeness, demanding responsiveness, appropriateness to users, update information and accuracy. Result of the correlation test between System Quality and Satisfaction towards System Quality presented that elements on simple function to learn and adjustable function according to the need of users correlated with the Satisfaction towards System Quality at high level and in positive way. Elements found in high level of correlation were respectively ranked as follows: the ease to learn, the simple function, and the adjustable function according to the need of users. Result of the correlation test between Service Quality and Satisfaction towards Service Quality presented that elements on immediate assistance from IT system administrator, proficiency of IT system administrator, ability to solve problems of IT system administrator, and determination and attention of IT system administrator correlated with the Satisfaction towards Service Quality at high level and in positive way. Elements found in high level of correlation were respectively ranked as follows: the ability to solve problems, the determination and attention, the immediate assistance, and the proficiency.